Associations of On-arrival Vital Signs with 24-hour In-hospital Mortality in Adult Trauma Patients Admitted to Four Public University Hospitals in Urban India: A Prospective Multi-Centre Cohort Study. Issue 5 (May 2021) - Sarang, Bhakti; Bhandarkar, Prashant; Raykar, Nakul; O'Reilly, Gerard M; Soni, Kapil Dev; Wärnberg, Martin Gerdin; Khajanchi, Monty; Dharap, Satish; Cameron, Peter; Howard, Teresa; Gadgil, Anita; Jarwani, Bhavesh; et al.
Highlights: Prospective multicentre cohort study It involves adult trauma patients at four public hospitals in urban India. 'Australia India Trauma Systems Collaboration' was created to facilitate trauma system development in India. It emphasizes on the development and implementation of a comprehensive trauma registry in LMICs. Study aims at analysing the associations of on-arrival vital signs with 24-hour in-hospital mortality. Abstract: Introduction: In India, more than a million people die annually due to injuries. Identifying the patients at risk of early mortality (within 24 hour of hospital arrival) is essential for triage. A bilateral Government Australia-India Trauma System Collaboration generated a trauma registry in the context of India, which yielded a cohort of trauma patients for systematic observation and interventions. The aim of this study was to determine the independent association of on-arrival vital signs and Glasgow Coma Score (GCS) with 24-hour mortality among adult trauma patients admitted at four university public hospitals in urban India. Methods: We performed an analysis of a prospective multicentre observational study of trauma patients across four urban public university hospitals in India, between April 2016 and February 2018. The primary outcome was 24-hour in-hospital mortality. We used logistic regression to determine mutually independent associations of the vital signs and GCS with 24-hour mortality. Results: A total of 7497 adult patients (18 years and above) were included. The 24-hour mortality was 1.9%. In univariable logistic regression, Glasgow Coma Score (GCS) and the vital signs systolic blood pressure (SBP), heart rate (HR), respiratory rate (RR) and peripheral capillary oxygen saturation (SpO2) had statistically significant associations with 24-hour mortality. These relationships held in multivariable analysis with hypotension (SBP<90mm Hg), tachycardia (HR>100bpm) and bradycardia (HR<60bpm), hypoxia (SpO2<90%), Tachypnoea (RR>20brpm) and severe (3-8) and moderate (9-12) GCS having strong association with 24-hour mortality. Notably, the patients with missing values for SBP, HR and RR also demonstrated higher odds of 24-hour mortality. The Injury Severity Scores (ISS) did not corelate with 24-hour mortality. Conclusion: The routinely measured GCS and vital signs including SBP, HR, SpO2 and RR are independently associated with 24-hour in-hospital mortality in the context of university hospitals of urban India. These easily measured parameters in the emergency setting may help improve decision-making and guide further management in the trauma victims. A poor short-term prognosis was also observed in patients in whom these physiological variables were not recorded.